Heat and the planning system: how can local authorities encourage deployment of low and zero-carbon heating? - Barns, David G.; Bale, Catherine S. E.; Taylor, Peter G.; Owen, Alice (Frontiers in Sustainable Cities, 2024)
There is widespread recognition of the need for new homes to feature only low or zero carbon (LZC) heating. However, residential developers continue to choose conventional high-carbon options such as natural gas boilers over Net Zero compatible alternatives. This study explores how UK Local Authorities (LAs) within the English planning system can encourage residential developers to deploy LZC heating systems within their projects. We adopt an embedded case study design and analyse 30 residential project proposals within two LA areas. Through documentary analysis and expert interviews with local stakeholders, we explore local planning policies adopted and interactions between developers and LA officers, along with the resultant outcomes. We find that LAs can encourage developers to adopt LZC heating technologies above and beyond that which is required nationally. The conditions for this to occur are: (1) a planning policy which restricts allowable heating technology options, (2) empowering LA officers to enforce policies, (3) advice and support for developers to consider alternatives, and where necessary, (4) political backing to challenge unwilling developers.